The validation of the malay version sino-nasal outcome test 22 (snot-22) in chronic rhinosinusitis patients - Zulkifli, Shifa Zulkifli (2013)
Objectives: To translate Sino-Nasal Outcome Test-22 into the Malay language and to determine the feasibility, validity and reliability of the Malay version of SNOT-22. Study Design and Methodology : This was a cross sectional study conducted at the ORL-HNS general clinic and rhinology clinic in HUSM. 70 CRS respondents were involved and 39 healthy participants recruited for the control group. The Malay translated SNOT-22 and a previously Malay validated SF-36 were administered by the respondents. The translation used forward, backward and respondent testing and has been reviewed for face and content validity. The Malay version of SNOT -22 was administered again at two to four weeks interval retesting 55 patients with CRS. The statistical analysis used was feasibility, cronbach's alpha, intraclass correlation coefficient, Pearson's correlation coefficient and factor analysis. Results : Regarding feasibility of this test, the response rate of each question items was 97.2% in the initial test and 100% in the retest. All items in SNOT-22 have means ranging from 1.10-2.64 with standard deviations ranged from 0.933- 1.486. The Cronbach's alpha was high that is 0.89 in the initial test. The average intraclass correlation coefficient {ICC) was high that is 0.90 indicating good testretest reliability. Factor analysis showed that Malay version SNOT -22 have four unique constructs that is the rhinological symptoms, ear or facial symptoms, sleep and psychological function. Discriminant validity demonstrate that Malay version SNOT-22 was able to discriminate between control group and patients (t=15.33; p<0.001). Concurrent validity findings showed that the subscale of Role Physical (RP) in Malay version SF-36 statistically correlates significantly with ear or facial symptoms (r=-0.259, p<0.05) and psychological issues (r=- 0.304, p<0.01) in Malay version SNOT-22. Bodily Pain (BP) domains in Malay version SF-36 also statistically significant with psychological issues (r-0.498, p<0.01) within Malay version SNOT-22. Most of the domains within Malay version SNOT-22 were weakly correlated with the scales of Malay version SF- 36. However, validity of the Malay version SNOT-22 as a reliable and valid tool for quality of life assessment is established by fulfillment of content, construct, and discriminant validity. Conclusions : The translation of the Malay version SNOT -22 was acceptable. Feasibility was present and scaling assumptions were met. The reliability was excellent and validity is established. SNOT-22 is recommended for Malaysia's clinicians and researchers as a patient reported measure of outcome in sino-nasal disorders such as rhinosinusitis and nasal polyposis.